Antimicrobial resistance and molecular characterization of methicillin-resistant coagulase-negative staphylococci from public shared bicycles in Tianjin, China. (December 2019) - Xu, Zhen; Liu, Shiyan; Chen, Liqin; Liu, Yuting; Tan, Long; Shen, Jun; Zhang, Wanqi
Highlights: S. epidermidis group is the pre-dominant species that were recovered from public shared bicycles. 49% staphylococcal isolates harboured the mecA gene. The resistant rate of penicillin and erythromycin in mecA positive staphylococci is much higher than that of mecA negative staphylococci Hospital associated SCC mec type I, II, III were prevalent among the isolates that were recovered from public shared bicycles. Public shared bicycles may act as the reservoir for antimicrobial resistant pathogenic bacteria. Abstract: Objectives: Methicillin-resistant coagulase-negative staphylococci (CoNS) have emerged as one of the major nosocomial pathogens, and antimicrobial resistance has aggravated the problem. Sixteen million public shared bicycles (PSBs) were launched in China, and 106 million users were recorded. However, no standard clean strategy has been applied to PSBs in China, and no formal surveillance has been carried out. The objective of this study was to understand the diversity and antimicrobial resistance of staphylococcal species from PSBs. Methods: Seventy-nine specimens and 128 isolates were collected from 79 PSBs in Tianjin city, China. Antimicrobial susceptibility and molecular testing were performed to understand the species, antimicrobial resistance, carriage of mecA gene, and clonal lineage. Results: Thirty-five staphylococcal isolates were identified, and 80% of staphylococci were resistant to at least one antibiotic. Seventeen (49%) staphylococci were mecA -positive. SCC mec type V (n = 5), SCC mec type 1A (n = 5), SCC mec type I (n = 3), SCC mec type III (n = 2), 1 SCC mec type II (n = 1), and SCC mec type IV (n = 1) were determined. In addition, Staphylococcus epidermidis ST5, ST35, ST234 and ST419 were determined, and a new ST (ST831) was also found. Conclusions: The Staphylococcus epidermidis group was prevalent among PSBs, and multiple resistant staphylococci were determined in this study. The diversity of SCC mec elements was observed, and PSBs may act as the reservoir for antimicrobial pathogenic bacteria. Moreover, additional studies are necessary to systematically understand the prevalence and molecular epidemiology of methicillin-resistant staphylococci in PSBs.